Investigating an Adapted Process Genre Writing Model and Its Implications for Undergraduate Thai Students - Sarath Withanarachchi Samaranayake; Patteera Thienoermpool; Suneeta Kositchaivat (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
Teaching academic writing to English as a Foreign Language (EFL) students poses significant challenges, often requiring instructors to adapt their instructional strategies to effectively meet learners' diverse needs and contexts. This study investigates the impact of an adapted process genre writing model, enhanced with teacher-prepared materials, on improving the academic writing proficiency of tertiary-level students at a public university in Thailand. A quantitative research method was employed for this study, involving a sample of 48 participants selected through convenience sampling. Over one semester, these students received intensive instruction based on the adapted process genre writing model. Data collection involved administering pre-and post-tests to measure changes in writing performance, with statistical analyses conducted using descriptive statistics and paired-sample t-tests to determine the significance of any improvements. The results revealed statistically significant improvements (p < .05) in participants' writing proficiency, demonstrating the effectiveness of the adapted process genre writing model. The results suggest that integrating customized instructional resources into this framework can significantly support the academic writing development of Thai EFL undergraduates. The study's implications for EFL instruction are substantial, suggesting that a well-structured, genre-based approach, supplemented with tailored instructional materials, can significantly elevate students' writing proficiency in academic contexts. Recommendations for further research include exploring the long-term effects of this instructional model on students' writing abilities and investigating its applicability across different language proficiency levels and cultural settings.